Integration of a knee flexor bias or hip hinge bias resistance training program with combined high-speed running in academy soccer players - Ross, S.; Ripley, N. J.; McMahon, J. J.; Comfort, P. (The Journal of Strength and Conditioning Research, 2025)
Strength training has been shown to mitigate risk of hamstring strain injury and enhance athletic performance. However, most training studies are focused on single exercise interventions and, therefore, lacking in ecological validity. In this study, we investigated the effects of combined resistance training and curvilinear high-speed running, with resistance training sessions having either a hip hinge bias (Romanian deadlift; RDL) or knee flexor bias (Nordic hamstring exercise; NHE), on knee flexor strength, jump, and sprint performance. In total, 37 male academy soccer players (17.1 ± 0.2 years; height, 178.3 ± 2.5 cm; body mass, 70.6 ± 0.7 kg) were randomized into 3 groups (RDL, NHE, and control) and completed 6 weeks of training. Knee flexor strength was improved in both intervention groups compared with the control (p = 0.05; g = 0.85-1.62); however, adaptations in sprint (g = 1.14-1.44) and jump performance (g = 1.08-1.57) were superior in the NHE group than in the RDL and control groups. The results of the study indicate that both interventions were effective in improving knee flexor strength and athletic performance, but interventions that include the NHE seem to be more effective.